Pengaruh Digital Governance terhadap GDP melalui E-Taxation dan E-Banking di Indonesia: Analisis Literatur Sistematis - Gilberth Suryadi; Mulyani Safira; Nindah Warachmah Suharji; Dini Hariyanti; Muhammad Zilal Hamzah (Jurnal Wacana Ekonomi, 2026)
Digital transformation in public governance and the financial sector has become a strategic driver of national economic growth. Digital governance plays a crucial role in improving bureaucratic efficiency, fiscal transparency, and the integration of public and financial services. This study aims to analyze the impact of digital governance on Gross Domestic Product (GDP) growth through two key instruments, namely e-taxation and e-banking in Indonesia. A Systematic Literature Review (SLR) method was employed, examining scientific publications and official institutional reports from 2020 to 2025. The analytical framework is based on Modernization Theory, the E-Government Maturity Model, and Fiscal Policy Transmission Theory. The findings indicate that strengthened digital governance positively contributes to increased tax revenues, expanded financial inclusion, and improved efficiency of the financial system, which indirectly supports GDP growth. The integration of e-taxation and e-banking within the digital governance framework enhances fiscal capacity, economic stability, and sustainable economic development.